Mental Health Problems and English Achievement of UNKLAB High School Students - Simanungkalit, Ate Gueen; Muhaling, Regina Octavia (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Klabat, 2023)
Abstract The main purpose of this study was to find out the correlation between mental health problems and English achievement of students at a private high school in Airmadidi, Indonesia. This study also explored the mental health problems that was categorized as depression, anxiety, and stress, and student English achievement. The results showed that the overall mental health problems were categorized in moderate level. The English achievement was categorized as below average. There was a significantly negative correlation between the student mental health problems and their English achievement. It signified that the higher score in the final test of English subject was significantly associated with lower mental health of the students. The higher the mental health problems, the lower the score in English final test of the students. Keywords: mental health, English achievement, depression, anxiety, stress.